Factors affecting women’s nutritional security in rural Bangladesh: The role of livestock and other socioeconomic characteristics - Fatema Tuj Zohora Hira; Mohammad Jahangir Alam; Ismat Ara Begum; Md. Abdullah Al Mamun; Md. Asif Iqbal; Farzana Yeasmin (PLoS ONE, 2025)
In every household, women play a crucial role in shaping the foundation of food and nutrition. They are primarily responsible for ensuring nutritional security for all members. However, women often find themselves in vulnerable positions within this context. With this in mind, the study aimed to evaluate the nutritional security status of women and explore its determinants. Data were extracted from the Bangladesh Integrated Households Survey-2018. A total of 5604 women were considered, and their nutritional security status was measured based on their minimum dietary diversity intake and sufficient calorie consumption in a 24-hour period. The data were divided into two subsets: households with livestock and households without livestock, to examine the impact of livestock ownership on women’s nutritional security status. The findings revealed that within the overall population, approximately 9% of women have achieved nutritional security. Interestingly, a higher proportion of women, around 11%, from households with livestock were found to be nutritionally secure compared to those without livestock, where only about 7% of women achieved nutritional security. A binary logit regression model was utilized to explore significant predictors and found that livestock ownership, women’s education level, household income, farm size, household size, ownership of a mobile phone by women, and women`s nutritional knowledge were significantly positively associated with their nutritional security status. When examining the subset of women from households without livestock, it was found that their monthly income, farm size, and women’s nutritional knowledge had insignificant impacts compared to women from households with livestock. Addressing the role of livestock, the study concludes that the predictors of women’s nutritional status are not equally significant based on livestock ownership. The study’s findings will assist in designing and formulating future policies and development programs addressing this newly acquired knowledge.